2018
DOI: 10.1136/jim-2017-000513
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Function and Peripheral Vascular Arterial Stiffness in Patients with Dipper and Non-Dipper Hypertension

Abstract: A non-dipper pattern of high blood pressure is associated with increased risk of organ damage and cardiovascular disease in patients with hypertension. The aim of the study was to evaluate the left ventricular (LV) remodeling and function and arterial stiffness in a dipper/non-dipper pattern of high blood pressure in patients with hypertension. A total of 183 hypertensive patients with no history of adverse cardiovascular events were divided into two groups based on 24 hours ambulatory blood pressure monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…Currently, there are several studies that have illustrated the pathological changes of the vascular wall that underlie cardiovascular events and play an important role in the progression of cardiovascular diseases [2][3][4]. Furthermore, changes in the structure of arterial wall caused declination in arterial compliance that might precede the clinical symptoms of the disease [5][6][7]. erefore, arterial elasticity and function are used as a variety of cardiovascular risk factors for subclinical vascular lesions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several studies that have illustrated the pathological changes of the vascular wall that underlie cardiovascular events and play an important role in the progression of cardiovascular diseases [2][3][4]. Furthermore, changes in the structure of arterial wall caused declination in arterial compliance that might precede the clinical symptoms of the disease [5][6][7]. erefore, arterial elasticity and function are used as a variety of cardiovascular risk factors for subclinical vascular lesions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in hypertensive patients, 3D echocardiography and strain echocardiography revealed subclinical changes in left ventricular systolic and diastolic function and left atrial function, which have not been demonstrated by conventional echocardiography. These new echocardiographic www.ah.viamedica.pl methods become important tools in evaluating the effect of the dipper versus non-dipper patterns on cardiac morphology and function in hypertensive patients [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2018 [20], conducted in treated hypertensive patients, where cardiac function beyond conventional echocardiography was also assessed by tissue Doppler and Speckle Tracking with Strain evaluation. In this study, the authors concluded important data on differences in morphology and cardiac function between the dipper vs. non-dipper patterns, demonstrating an association between nondipper pattern and LV remodeling, diastolic dysfunction and reduction of myocardial strain also compatible with LV systolic dysfunction and they alert that patients with uncomplicated hypertension should always consider performing ABPM or another innovative method that provides information on the nocturnal blood pressure pattern to better stratify cardiovascular risk and delineate therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Due to BP fluctuation, dipper hypertension is defined as nocturnal BP decline with a normal fall > 10%, and non-dipper hypertension is defined as a circadian rhythm over 24 h with abnormal fall < 10% at night with organ damage (heart, brain and kidney), high risk of cardiovascular and cerebrovascular diseases, and adverse outcomes (Chen et al, 2018;Kario et al, 2001;Kurpesa et al, 2002;Zhu, 2015). Staessen et al reported both the blood pressure decrease and ratio that showed a curvilinear correlation with age and the smallest decrease and largest ratio were observed in older (≥ 70 years) subjects (Staessen et al, 1997).…”
Section: Anti-hypertension Efficacymentioning
confidence: 99%